Analisis Indeks Pembangunan Manusia (IPM) dalam Perspektif Ekonomi Islam: Studi Konseptual dan Relevansinya terhadap Tujuan Maqashid Syariah - Nurrahman, Ahmad Gemma; Miptahudin, Iip; Fajrussalam, Hisny; Rhommadhonni, Vania Nur Rizqi; Prabandari, Fitriana (STAI Al Musaddadiyah Garut, 2025)
This study aims to analyze the Human Development Index (HDI) from the perspective of Islamic economics and to examine its relevance to the objectives of Maqashid Sharia. HDI, as a development indicator that includes the dimensions of education, health, and income, reflects the overall quality of life within a community. In Islamic economics, human development is understood more comprehensively, encompassing material, spiritual, and moral well-being; therefore, HDI has a clear point of alignment with core Islamic values. This research employs a qualitative-descriptive approach through a literature review, examining various publications related to HDI, Islamic economic principles, and the concept of Maqashid Sharia. The findings indicate that the components of HDI are significantly connected to the five primary objectives of Maqashid Sharia, namely the preservation of religion (hifzh al-din), life (hifzh al-nafs), intellect (hifzh al-‘aql), lineage (hifzh al-nasl), and wealth (hifzh al-mal). This connection highlights that human development, as measured by HDI, can be strengthened through a Sharia-based framework to ensure it is not only focused on statistical progress but also on building ethical, empowered, and just individuals. Therefore, integrating HDI with the principles of Maqashid Sharia offers a relevant and applicable strategy for achieving sustainable development aligned with Islamic values. Keywords : Human Development Index, Islamic Economics, Maqashid Syariah, Sustainable Development, Welfare.